Stathmin-2 enhances motor axon regeneration after injury independent of its binding to tubulin - Melinda S. Beccari; Olatz Arnold-Garcia; Michael W. Baughn; Jonathan W. Artates; Melissa McAlonis-Downes; Jaisen Lim; Dulce Fernanda Leyva-Cázares; Hugo Isaac Rubio-Lara; Andrea Ramirez-Rodriguez; Carol N. Bernal-Buenrostro; Brian Murgia-Bay; Carolina K. Rangel; et al. (Proceedings of the National Academy of Sciences, 2025)
Stathmin-2 (also known as SCG10 ) is encoded by the STMN2 gene, whose mRNA is one of the most abundantly expressed in human motor neurons. In almost all instances of ALS and other TDP-43 proteinopathies, stathmin-2 encoding mRNAs are cryptically spliced and polyadenylated in motor neurons, a pathogenic consequence of nuclear loss of function of the RNA binding protein TDP-43. While stathmin-2 has been shown to enhance regeneration after axonal injury to axons of cultured motor neurons, here, we show that after crush injury within the adult murine nervous system of wild-type or stathmin-2-null mice, the presence of stathmin-2 reduces axonal and neuromuscular junction degeneration and stimulates reinnervation and functional recovery. Mechanistically, although stathmin-2 has been proposed to function through direct binding to α/β tubulin heterodimers and correspondingly to affect microtubule assembly and dynamics, stathmin-2’s role in axon regeneration after axotomy is shown to be independent of its tubulin binding abilities.